2020
DOI: 10.1177/0143034320961465
|View full text |Cite
|
Sign up to set email alerts
|

Discipline, motivation, and achievement in mathematics learning: An exploration in Shanghai

Abstract: Utilizing the Programme for International Student Assessment 2012 Shanghai dataset ([Formula: see text]), this study examined the relationship between school disciplinary climate aggregated from mathematics classrooms and student mathematics learning outcomes, including mathematics achievement and intrinsic and instrumental motivation to learn mathematics, from the perspective of the self-determination theory of academic motivation. The results of the analyses demonstrated challenges supporting students in Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
(35 reference statements)
0
12
0
1
Order By: Relevance
“…Further analysis revealed that the reason is that the impact of the mastery goal orientation on student reading literacy can be weakened by both a more positive school disciplinary climate level and strong climate strength, but be enhanced by both a more negative school disciplinary climate level and weak climate strength. On the one hand, it is possible that a highly ordered school disciplinary climate would undermine student sense of self-determination, intrinsic motivation (Kover and Worrell, 2010 ), and autonomy (Ning, 2020 ), especially in East Asian cultures, where an orderly learning atmosphere and explicit rules are established to hinder distraction, noise, and disorder in the classroom (Ning, 2019 , 2020 ), which could easily lead to the weakening of students' tendency to mastery goals. On the other hand, although the negative and weak school disciplinary climate always means loose school management, students under higher self-management ability and autonomy are more likely to tend to mastery goals and then take the initiative to utilize abundant resources to make academic progress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further analysis revealed that the reason is that the impact of the mastery goal orientation on student reading literacy can be weakened by both a more positive school disciplinary climate level and strong climate strength, but be enhanced by both a more negative school disciplinary climate level and weak climate strength. On the one hand, it is possible that a highly ordered school disciplinary climate would undermine student sense of self-determination, intrinsic motivation (Kover and Worrell, 2010 ), and autonomy (Ning, 2020 ), especially in East Asian cultures, where an orderly learning atmosphere and explicit rules are established to hinder distraction, noise, and disorder in the classroom (Ning, 2019 , 2020 ), which could easily lead to the weakening of students' tendency to mastery goals. On the other hand, although the negative and weak school disciplinary climate always means loose school management, students under higher self-management ability and autonomy are more likely to tend to mastery goals and then take the initiative to utilize abundant resources to make academic progress.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of evidence, most school disciplinary climate studies have paid more attention to climate level and little focus on climate strength (Guo et al, 2018). These studies mainly supported the positive association between disciplinary climate level and academic behavior (Arum and Velez, 2012;Frempong et al, 2012;Cheema and Kitsantas, 2014;Ning et al, 2015;Jenkins and Ueno, 2017;Chi et al, 2018;Guo et al, 2018;Ning, 2019Ning, , 2020, including reading achievement (Ning et al, 2015). Meanwhile, Guo et al (2018) highlighted the positive effect of disciplinary climate strength on student reading performance.…”
Section: School Disciplinary Climatementioning
confidence: 98%
See 1 more Smart Citation
“…Particularly, students from East-Asian countries, such as China, tend to spend more time taking classes and doing homework and perceive more academic stress than students from Western countries do (Ye et al, 2019). Due to highly valued academic achievement in traditional Chinese culture, academic performance has become a concern among Chinese adolescents and their parents as well as educators and administrators, which results in exam-oriented education, excessive stress, orderly school disciplinary climate, and lack of academic motivation (Sun et al, 2013;Ye et al, 2019;Ning, 2020).…”
Section: Academic Stress and Physical Education In Chinamentioning
confidence: 99%
“…To test the theoretical assumptions mentioned above, previous studies have reported that learning motivation is related to students' mathematics achievement (El-Adl & Alkharusi, 2020;Ning, 2020;Nugraha, Nugraha, & Widyastuti, 2021). It was also reported that tutoring is also related to student achievement.…”
Section: Introductionmentioning
confidence: 98%